PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP LOYALITAS PASIEN RSIA ERIA BUNDA PEKANBARU - Eko Risky; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Quality of service is how far the difference between the reality and expectations of consumers for the services they receive or earn. Brand image is a way for companies to introduce their companies to customers and to attract customers to the company. Loyalty is described as the customer's desire to subscribe to the company continuously, buying and using the company's products and services repeatedly, and recommending the product to the company to others. This research was conducted on RSIA Eria Bunda Pekanbaru which is located at JL.K.H.Ahmad Dahlan No.163 Sukajadi-Pekanbaru.This study aims to determine the effect of service quality and brand image on customer loyalty at RSIA EriaBundaPekanbaru. In this research data analysis used descriptive and quantitative. The sample in this research totaled 100 respondents, with sampling method using a purposive sampling. Data collection techniques used are primary and secondary data through observation, interview, and questionnaire. Method of data analysis used simple linear regression analysis method and multiple linear regression.From the results of tests conducted indicate that service quality and brand image have a positive and significant impact on customer loyalty in RSIA Eria Bunda Pekanbaru.Keywords : Service Quality, Brand Image dan Patient Loyalty.